FAKTOR YANG MEMPENGARUHI RESILIENSI PADA NARAPIDANA PERE MPUAN KASUS WANITA TUNA SUSILA DI LAPAS PEREMPUAN KELAS IIB BENGKULU - Siahaan, Sella Efita; Biafri, Vivi Sylviani (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Prisoners experience various things, such as losing their sense of security and comfort and even losing self-control. They lose their freedom and independence in prison where they have to live a life they never wanted before, they are not allowed to associate with members of the same sex, they lose the ability to make all their own decisions and they lose their capacity for help and services. This research aims to determine and analyze the factors that support resilience in female prisoners in the case of prostitutes at the Class IIB Bengkulu Women's Penitentiary. This research method uses a qualitative approach. The research shows that the factors influencing resilience are individual characteristics, family influence, and the environment. Based on the research results, it is known that all informants have been able to identify the causes of the problems they face such as feeling sad when they had to leave their family, longing for home and family, and the desire to go home immediately. Keywords: Resilience; Correctional Institutions; Prostitution Prisoners